Madurese Migrants Socioculture and Early Childhood Parenting: A Case Study in the Sombo Kampong Sidotopo Sub District Semampir District of Surabaya, East Java, Indonesia - Lestari, Gunarti Dwi; Supriyono, Supriyono; Mundhir, Mundhir; Rasyad, Ach (Universitas Negeri Semarang, 2017)
This study aims to analyze sosiokultur Madurese migrants in Sombo kampong, nurture their early childhood, and the construction of meaning model of early childhood care are regarded as unique. This research approach is qualitative case study type. Data were collected through interviews, observation, and documentation. The findings show that Madurese socioculture migrants in Sombo kampong can be seen from several aspects of life, that they are people who: (1) obey the teachings of Islam; (2) very obedient, submissive, and resigned and hierarchically to Buppa, '(father), Babbu (mother), teachers or Kyai, and Rato (government leaders); (3) has a uniqueness in maintaining kinship, (4) in an effort to establish kinship done by following the recitation, tiba'an, and arisan; (5) irritable, loud, temperamental, vindictive, irritable, and easily suspicious of other people who were suspected; (6) to migrate to survivalitas and dignity; (7) working any lawful as long as it gets results; (8) live in rented rooms, a densely populated neighborhood, slum, and difficult access to clean water; (8) have the courage, firmness, and self-confidence to survive; (9) often received threats of physical violence from colleagues who continues with carok and mostly peacefully; (10) has the openness and honest; (11) said the language is straightforward and rugged; and (12) if receiving insults almost certainly upset with the various levels and forms.